2019
DOI: 10.1007/978-3-030-20887-5_28
|View full text |Cite
|
Sign up to set email alerts
|

VIENA $$^2$$ : A Driving Anticipation Dataset

Abstract: Action anticipation is critical in scenarios where one needs to react before the action is finalized. This is, for instance, the case in automated driving, where a car needs to, e.g., avoid hitting pedestrians and respect traffic lights. While solutions have been proposed to tackle subsets of the driving anticipation tasks, by making use of diverse, taskspecific sensors, there is no single dataset or framework that addresses them all in a consistent manner. In this paper, we therefore introduce a new, large-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…We present our results for VIENA 2 dataset in Table 2, where we compare our class-wise accuracy scores (obtained with E r×c,16 ) with that of Aliakbarian et al [9] (obtained on the visual and sensor data, at the end of the 5 th second). In the experiments E r×c, 16 , we found that the class-wise accuracy scores for each Scenario plateaus after the 50 th epoch, with slight fluctuations later (total number of epochs run -64).…”
Section: Viena 2 Dataset Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We present our results for VIENA 2 dataset in Table 2, where we compare our class-wise accuracy scores (obtained with E r×c,16 ) with that of Aliakbarian et al [9] (obtained on the visual and sensor data, at the end of the 5 th second). In the experiments E r×c, 16 , we found that the class-wise accuracy scores for each Scenario plateaus after the 50 th epoch, with slight fluctuations later (total number of epochs run -64).…”
Section: Viena 2 Dataset Resultsmentioning
confidence: 99%
“…Torstensson et al [8] proposed a Convolutional and LSTM based network to predict the actions of the in-vehicle driver. In a work related to Driving Action Anticipation, Aliakbarian et al [9] introduced a new dataset: VIENA 2 and proposed a multi-modal LSTM based network to forecast driver actions from visual and sensor data.…”
Section: Driving Scene Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…These create predictions directly from observed features. Examples include F-RNN-EL [226] which uses an exponential loss to bias a multi-modal CNN+LSTM fusion strategy towards the most recent predictions, MS-LSTM [227] which uses two LSTM stages for action-aware and context-aware learning, MM-LSTM [228] which extends MS-LSTM to arbitrarily many modalities, FN [229] which uses a three-stage LSTM approach, and TP-LSTM [230] which uses a temporal pyramid learning structure.…”
Section: ) Action Prediction Modelsmentioning
confidence: 99%
“…There are a number of datasets that cater to pedestrian crossing prediction [8], [9], [12], [13], [14]. They contain video clips annotated with 2D bounding boxes and behavioural tags for pedestrians.…”
Section: Introductionmentioning
confidence: 99%